The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1086/338456
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Proenteropeptidase Gene Are the Molecular Cause of Congenital Enteropeptidase Deficiency

Abstract: Enteropeptidase (enterokinase [E.C.3.4.21.9]) is a serine protease of the intestinal brush border in the proximal small intestine. It activates the pancreatic proenzyme trypsinogen, which, in turn, releases active digestive enzymes from their inactive pancreatic precursors. Congenital enteropeptidase deficiency is a rare recessively inherited disorder leading, in affected infants, to severe failure to thrive. The genomic structure of the proenteropeptidase gene (25 exons, total gene size 88 kb) was characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 22 publications
2
53
0
Order By: Relevance
“…The activated trypsin in turn activates downstream digestive enzymes, such as chymotrypsinogen, proesterase, procarboxypeptidases A and B, and prolipase, which allow the absorption of amino acids and triglycerides in the gut . Congenital enteropeptidase deficiency in humans has resulted in intestinal malabsorption and a lean phenotype, which suggest the pivotal role of this enzyme in regulating body homeostasis . Interestingly, a recent seminal study suggested that inhibiting gut enteropeptidase may be a novel strategy for correcting obesity .…”
Section: Introductionmentioning
confidence: 99%
“…The activated trypsin in turn activates downstream digestive enzymes, such as chymotrypsinogen, proesterase, procarboxypeptidases A and B, and prolipase, which allow the absorption of amino acids and triglycerides in the gut . Congenital enteropeptidase deficiency in humans has resulted in intestinal malabsorption and a lean phenotype, which suggest the pivotal role of this enzyme in regulating body homeostasis . Interestingly, a recent seminal study suggested that inhibiting gut enteropeptidase may be a novel strategy for correcting obesity .…”
Section: Introductionmentioning
confidence: 99%
“…Only 13 cases of primary enterokinase deficiency have been reported. Three additional patients were reported with a similar clinical picture, but with unmeasured intestinal enterokinase activity [23]. All mutations identified in the proenteropeptidase gene are null mutations that predict the absence of a correctly formed active site.…”
Section: Enterokinase Deficiencymentioning
confidence: 97%
“…Proteinase-activated receptor 2 is present at the apical and basolateral membrane of enterocytes; activation of this receptor by trypsin stimulates enterocytes to secrete eicosanoids, which act locally in the intestinal wall to regulate epithelial growth [23]. Therefore, in addition to its purely digestive role, enterokinase localization on the luminal surface of the duodenal villi possibly contributes to enterocyte growth by generating active trypsin on the cell surface.…”
Section: Enterokinase Deficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…3 4 Loss of function mutations in enterokinase cause congenital enteropeptidase deficiency with retardation of growth during childhood, chronic diarrhoea, and generalised oedema. 5 This severe protein malabsorption is prominent during childhood and corresponds to a lack of enterokinase dependent activation of digestive enzymes.…”
Section: Digestionmentioning
confidence: 99%